2020
DOI: 10.3390/ijerph17207383
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic and Its Impact on Homebound Nursing Students

Abstract: University students are predisposed to stress, which could be even higher in Nursing students since they are directly related to the COVID-19 pandemic given their health training and area of knowledge. Our purpose was to assess the stress levels of Nursing students before and during lockdown due to the COVID-19 pandemic in Murcia (Spain), its influence on taking an online exam and how it was affected by physical exercise. This was an observational and prospective study including Nursing students from the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
2
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 25 publications
8
112
2
14
Order By: Relevance
“…The relationship between perceived stress and aspects of mental health has been well-established in university students and it is therefore unsurprising that this link has remained throughout the COVID-19 pandemic [ 7 , 41 ]. However, in contrast to early findings, the current study found no relationship between physical activity levels and mental wellbeing [ 3 , 11 , 16 , 17 , 18 , 19 ]. Importantly, this may be driven by the finding that the average MVPA per week in the present population was 173 min, thereby remaining above the recommended guideline of 150 min and not affecting mental wellbeing.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The relationship between perceived stress and aspects of mental health has been well-established in university students and it is therefore unsurprising that this link has remained throughout the COVID-19 pandemic [ 7 , 41 ]. However, in contrast to early findings, the current study found no relationship between physical activity levels and mental wellbeing [ 3 , 11 , 16 , 17 , 18 , 19 ]. Importantly, this may be driven by the finding that the average MVPA per week in the present population was 173 min, thereby remaining above the recommended guideline of 150 min and not affecting mental wellbeing.…”
Section: Discussioncontrasting
confidence: 99%
“…Initial studies reported that student mental health and movement behaviours were impaired during the initial phases of the pandemic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 ], but these studies may no longer be reflective of current trends. Recent findings have indicated that people within the UK general population are becoming accustomed to the new psychological demands of life in lockdown and as a result, mental health is stabilising from high levels of anxiety and depression initially observed during the early stages of the pandemic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, many previous studies showed that psychological problems of medical students may affect the choice of medical career and even lead to students' suicide (5)(6)(7). Currently, only several studies have reported nursing students' sleep quality and their stress levels before and during lockdown due to the COVID-19 pandemic (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%